Practice of Administrative and Jurisdictional Activity of Community Police Officers – Integral Part of the Principles for the Formation of Local and State Security Policy - M. V. Kalashnyk (Law and Safety)
The author has accomplished the analysis of the essence of organizational and legal principles of community police officers’ activity (hereinafter – CPO), their interaction with other divisions of the National Police of Ukraine, state authorities, local self-government agencies and communities. The author has analyzed a set of tasks, functions and powers of CPO and the current state of regulatory legal provision of community police officers activity: has outlined the algorithm of actions of community police officers within the combination of functions of district police officers and patrol police officers.